Bayesian Analysis of Dietary Diversity among Lactating Mothers in Finote Selam District, Northwest Ethiopia: A Cross-Sectional Study. - Gebrie, Yenesew Fentahun; Dessie, Tadesse Mihretie (BioMed Research International, 2021)
Background. Dietary diversity is an essential element of diet quality. Lactation is one of the most complex and nutritionally demanding phases of the human life cycle, and the breastfed infant is dependent on mother nutrition. The objective of this study was to assess the prevalence of dietary diversity and its predictors among lactating mothers. Methods. A cross-sectional study design was employed in January 2020 among 416 lactating women using systematic sampling techniques. Data was collected using a structured interviewer-administered questionnaire. Bayesian estimation was used on logistic regression to identify the significant predictors of dietary diversity. Convergence of algorithm was assessed by using time series plot, density plot, and autocorrelation plot. Result. The prevalence of adequate dietary diversity was 23.1%, and the significant predictors of dietary diversity were marital status of mother, education of spouse, occupation of mother and spouse, family size, gravidity, ANC follow up, nutritional education, wealth index, and food security status. Conclusion. From the result, unmarried, having more family size, multigravidity, poor wealth indexed, and food in secured women were less likely to have adequate dietary diversity, whereas employed women, having ANC follow up and nutrition education, were strongly associated with adequate dietary diversity. Family planning should be given to minimize the impact of large family size of dietary diversity. Any concerned body should give attention to minimize food insecurity of lactating women. Attention should be given for ANC follow-up and nutritional education of mothers by health professional and policy maker.